Non-Structural Carbohydrate Content in Cryptogamic Antarctic Species After Two Years of Passive Warming on the Fildes Peninsula - Zuniga-Navarro, G; Cordero-Carrasco, R; Pizarro-Rojas, M; Caballero-Tellez, M; Casanova-Katny, A (EMUNI Press, 2015)
Cryptogamic vegetation dominates the ice-free areas of the maritime Antarctic. This particular flora grows slowly due to extreme environmental conditions, typically low temperature that may limit growth during a short summer. Over the last 50 years, the Antarctic Peninsula has undergone the highest registered temperature increases in Antarctica. As a consequence of higher temperatures, we hypothesized that lichens and mosses would produce more carbohydrates. To test this, open top chambers (OTCs) were installed in an Usnea-Himantormia community on Fildes Peninsula of King George Island. After two years, lichen thalli and plant tissues were collected to quantify non-structural carbohydrates in three lichens and two mosses. Responses contrasted between species. While non-structural carbohydrates were higher in the OTC for the lichen Himantormia lugubris, the values decreased in the moss Polytrichastrum alpinum. No marked responses to experimental warming were observed in the other three species. A significant species-specific increase in soluble sugar was observed inside the OTCs, while polyols content were not markedly different due to OTC treatment. In general, the obtained results indicate that warming does not increase carbohydrate content in all cryptogams, instead suggesting a strong species-specific response to a scenario of global warming. Further long-term warming experiments are needed to assess the responses of target species in the terrestrial Antarctic ecosystem.